HEALTH AND LEISURE: a study on the intensity of heart rate in children 6 to 9 years in Santa Cruz do Sul – RS - Kleinert, Daiana Luiza (2013)
In play, the child live experiences, performs social and emotional exchanges, assisting in their full development. The study is to describe the characteristics that mark the heart rate of children, during the course of recreational activities different Ways. They are subjects of this study, 30 students of both sexes, aged between 6 and 9 years old, belonging to a private school in the village of Santa Cruz do Sul. The methodological approach is descriptive and exploratory, and often made collection of heart rate at rest and during exercise in children, during the course of recreational activities and after the organization of the study data. The results show that the activity that increased intensity oh heart rate in children was the catch-up, reaching an average of 184,37 BPM for boys and girls 196,64 BPM. The activity increased less than the intensity of heart was to assemble the puzzle, reaching an average of 113,79 BPM for boys and girls 133,73 BPM. It was concluded that in all recreational activities of the circuit, the girls had higher heart rate higher than boys, both at home, and during activity and recovery.